Implementation of the Smart City Concept in the Dimensions of Smart People, Smart Mobility, and Smart Governance for the Realization of Jakarta Smart City - Tasa Aviana Rizki Amalia; Fridayani Helen Dian; Isnadi Yuli (SHS Web of Conferences)
This research aims to see how the implementation of the Smart City concept at DKI Jakarta especially on the smart people, smart mobility, and smart governance dimensions to realize Jakarta Smart City. Jakarta’s seriousness in developing the Smart City concept to provide services and public welfare that are more efficient, effective, and sustainable can be seen from the IMD Smart City Report 2023, where Jakarta is ranked 102 out of 141 cities in the world, outperforming two other Indonesian cities, Medan and Makassar. This research uses qualitative descriptive methods based on secondary data from digital news media. The data is processed using NVivo 14 as a research tool. Based on the results of research, it was found that the implementation of the Smart City concept at Jakarta showed that (1) Smart People, with the development of the digital society; (2) Smart Mobility, has been available integrated public transportation; (3) Smart Governance, which is marked by the policies that have been established in connection with the application of the smart city concept. This also showed that the implementation of Smart City concepts in Jakarta has gone well and continues to develop until now.